Analisis Resepsi Identitas Keindonesiaan Dalam Tayangan Indonesia Punya Cerita Di Trans TV - Azis, Abdul; Ginting, Reza Pahlevi (Jurnal Ilmiah Kanderang Tingang, 2024)
This study explores audience interpretations of the television program "Indonesia Punya Cerita" on Trans TV in relation to issues of Indonesian identity in television broadcasts. "Indonesia Punya Cerita" was selected because it is one of the few television shows that not only caters to market demands but also promotes themes of nationalism and Indonesian identity. Additionally, the show’s unique packaging style distinguishes it from other similar programs. This research employs a qualitative approach, utilizing in-depth interviews to collect data from informants with diverse socio-cultural backgrounds. The information gathered is analyzed using Stuart Hall’s Encoding-Decoding Reception Analysis Method, which categorizes audience interpretations into three positions: dominant hegemonic, negotiated, and oppositional. In reception analysis, the audience is seen as part of Interpretative Communities that are actively engaged in perceiving messages and producing meanings, thereby being active Producers of Meaning. The results reveal diverse interpretations among informants; however, most informants adopt an oppositional stance in interpreting the program. Interestingly, the oppositional interpretations are not limited to informants with postgraduate educational backgrounds but also include those with secondary education. For the informants, "Indonesia Punya Cerita" is merely a television show without significant impact.